Recall or transfer? How assessment types drive text-marking behavior - Marzouk, Zahia; Winne, Philip H. (Frontiers in Education, 2025)
IntroductionText marking is a widely used study technique, valued for its simplicity, and perceived benefits in enhancing recall and comprehension. This exploratory study investigates its role as an encoding mechanism, focusing on how marking impacts recall and transfer when learners are oriented toward different posttest items (recall or transfer).MethodWe gathered detailed data describing what learners were studying and how much they marked during studying. Participants were randomly assigned to one of four groups in a 2 × 2 factorial design. One independent variable, examples, determined whether participants were trained using examples of the types of information required to answer posttest items. The other independent variable, orientation, determined whether participants were instructed to prepare for a recall test or for an application (transfer) test.ResultsStatistical analysis revealed a detectable effect of study orientation (transfer vs. recall), F = 2.076, p = 0.043, partial η2 = 0.114. Compared to learners oriented to study for recall, learners oriented to study for transfer marked information identified as examples (F = 3.881, p = 0.051, partial η2 = 0.028), main ideas (F = 7.348, p = 0.008, partial η2 = 0.051), and reasons (F = 5.440, p = 0.021, partial η2 = 0.038). Moreover, a statistically detectable proportional relationship was found between total marking and transfer performance (F = 5.885, p = 0.017, partial η2 = 0.042). Learners who marked more scored higher on transfer questions. Prior knowledge mediated approximately 52% of the effect, indicating that as prior knowledge increased, so did the frequency of marking.DiscussionOrienting to study for a particular type of posttest item affected studying processes, specifically, how much learners marked and the categories of information they marked. While the frequency of marking was proportional to achievement, orienting to study for recall versus transfer posttest items had no effect on recall or transfer. Prior knowledge powerfully predicted how much learners marked text.